Juridical Analysis of Extortion that Occurred in the Umbul Ngrancah Tourism Village, Udanwuh Village, Semarang Regency - Walidi, Walidi; Priyo Agus Santoso, Aris; Habib, Muhamad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Illegal Levies or also known as extortion is an act of extortion that is prohibited in criminal law. This action is practically carried out in the form of a request for additional fees beyond the mandatory fees that have been specifically determined by a statutory regulation. This study aims to analyze the mechanism of law enforcement carried out against perpetrators of Extortion in the Umbul Ngrancah Tourism area, Udanwuh Village. This research uses a type of empirical juridical research. Extortion itself is often carried out by government officials or employees. The term extortion has become a trend again with Presidential Decree No. 87 concerning the 2016 Extortion Task Force, the Cyber Extortion Task Force was formed